Application of load transfer method for bored pile in loess area. Issue 10 (27th July 2022) - Zhou, Zhijun; Zhang, Zhipeng; Chen, Chaoran; Xu, Fu; Xu, Tianyu; Zhu, Linxuan; Liu, Tong
Abstract: This paper presented trilinear load transfer models for both pile shaft-–soil system and pile tip-soil system to analyze the load–settlement relationship of bored pile in loess area. Based on the differential equation of load transfer, the load transfer functions in different stages were deduced. Furthermore, combined with the trilinear model of pile tip-soil system, the load-settlement functions were obtained and the calculation method was completed. A static load test for a single pile was then carried out to obtain the required pile-soil system parameters, and the calculated results were presented and compared to those of the static load test, proving the feasibility of the proposed method. Moreover, the influence of each pile-soil system parameters on the load–settlement relationship of single pile was studied, and the results provide guidance for the pile foundation engineering in loess area.